Are Preferential Trade Agreements with Non-trade Objectives a Stumbling Block for Multilateral Liberalization? - Limão, Nuno (Review of Economic Studies, 2007)
In many preferential trade agreements (PTAs), countries exchange not only reductions in trade barriers but also cooperation in non-trade issues such as labour and environmental standards, intellectual property, etc. We provide a model of PTAs motivated by cooperation in non-trade issues and analyse its implications for global free trade and welfare. We find that such PTAs increase the cost of multilateral tariff reductions and thus cause a stumbling block to global free trade. This occurs because multilateral tariff reductions decrease the threat that can be used in PTAs and thus the surplus that can be extracted from them. By explicitly modelling the interaction between preferential and multilateral negotiations, we derive a testable prediction and provide novel econometric evidence that supports the model's key prediction. The welfare analysis shows that the current World Trade Organization rules allowing this type of PTAs may be optimal for economically large countries, thus the model can predict the rules we observe. We also analyse alternative rules that constitute a Pareto improvement. Copyright 2007, Wiley-Blackwell.